An outbreak of gastroenteritis by Salmonella enterica subspecies diarizonae - Vikrant Negi (Archives of Clinical Gastroenterology - Peertechz Publications, 2020)
Gastroenteritis in human by Salmonella enterica subspecies diarizonae is rare and usually observed in neonates and children with history of contact with reptiles. Salmonella enterica subspecies diarizonae were isolated from two young adult male patients with symptoms of acute gastroenteritis. The isolates were identified by Vitek 2 compact system and agglutination by specific antisera. The isolates were susceptible to Amikacin, Imipenam, Cefazolin and Ceftazidime. Patient rapidly responded to Amikacin and Ceftazidime therapy. Arizona group Salmonella should be looked in cases of gastroenteritis whenever there is history of proximity with reptiles.